A new basal titanosaur (Dinosauria, Sauropoda) from the Lower Cretaceous of Brazil - Carvalho, Ismar de Souza (2017)
Although dinosaurian ichnofaunas are common in the Northeastern Brazilian Interior Basins, osteological remains are poorly represented in these areas. One of the main challenges in vertebrate paleontology in the Lower Cretaceous of this region is to recognize body-fossils, which can unveil the anatomy, functional morphology and paleoecological aspects of the dinosaurian fauna recorded until now only by footprints and trackways. The discovery of a new dinosaur specimen in the Rio Piranhas Formation of the Triunfo Basin opens new perspectives into the comprehension of paleogeographical and temporal distribution of the titanosaur sauropods. Titanosaurs are common in Upper Cretaceous rocks of Brazil and Argentina. The age of the Rio Piranhas Formation is considered to range from Berriasian to early Hauterivian. Thus, the description of this new species opens new viewpoints concerning the paleobiogeographical aspects of these sauropod dinosaurs.